Imam al-Baghawy and his exegetical methodology in display verses of provisions - Saah, Fahkri (Al-HIKMAH Journal, 2021)
Commentary study is one of the noblest studies because it is regarding the holy book "Quran". Seeking in this study is considering one of the best kinds of worshipping god. So, start the Quran has been revealed to the prophet Muhammad peace be upon him scholars didn't stop hardworking for commentary the Quran in right exegetical methodology. Among them, Imam al-Baghawi died in 510 AH. It is an honor for me to have a study of Imam al-Baghawi and his exegetical methodology in-display verses of provisions. This study contributes to the knowledge of the origins upon which the interpreter was based in his commentary, as it provides the researcher with the abilities through which he can balance between sayings, and he knows the correct one from the weak.